THE EFFECT OF ROLE PLAY ON IMPROVING STUDENTS’ SPEAKING ABILITY: A LIBRARY RESEARCH (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research aimed to investigate how existing literature discusses the effect of role play as one of teaching technique on students’ speaking ability. This is a library research project conducted by critically reading eleven journal articles on the use of role play technique for students as the sources of data. The data were analyzed by implementing role play can improve students’ speaking ability. The result of data analysis showed that role play has been proven in the existing literature as a technique that can improve students’ speaking ability. The findings show that the use of role play enables the students to formulate and give them a better opportunity to improve their English speaking ability. It is also proven that role play provides the students a chance to explore different situations of real life and enables them to speak accurately and confidently.Key Words: Role Play, Speaking Ability, Improving, Library Research.